A relação entre tempo e narrativa no pensamento de Paul Ricoeur: a leitura do Livro XI das Confissões de Agostinho - Marques, Juliana das Neves Correa (2025)
This paper investigates Paul Ricoeur’s reading of Book XI of Augustine’s Confessions, as developed in Temps et Récit. The main objective is to identify elements in Augustine’s work that support Ricoeur’s thesis that time becomes human as it is narratively structured. To guide our research, we have formulated some central and general questions that we seek to answer throughout this investigation, namely: In what way does Augustine attempt to solve the enigma of time? What elements does Ricoeur find in Book XI that support his thesis that the solution to the paradoxes of time is narrative? Does Ricoeur ignore the relationship between time and eternity in his interpretation of Book XI of Confessions? To answer these questions, it is necessary to reconstruct Augustine’s meditation contained in Book XI of Confessions, in light of Ricoeur’s reading as presented in Temps et Récit. Augustine suggests a subjective conception of time, experienced internally in the soul as distentio animi (the distension of the mind). To reach this conclusion, Augustine reflects on the relationship between time and eternity, the ontological paradoxes of being and non-being of time, and the measurement of time. He contrasts the skeptical argument, which denies the existence of time, with everyday language, which inexplicably suggeststhat time doesindeed exist. Itseems that, in examining Augustine’s meditation on time, Ricoeur perceives that the Christian philosopher, in attempting to explain time, necessarily resorts to narrative, although without realizing it. Thus, Ricoeur argues that time only becomes human when it is narrated. For him, time acquires meaning and dimension through narrative, becoming incomprehensible otherwise: time exists because we narrate it.